The role of exercised-based cardiac rehabilitation in unrevascularized complex coronary artery disease patients: a case series - Aryanugraha, Teguh; Tjahjono, Cholid Tri; Mayangsari, Veny; Satrijo, Budi; Anjarwani, Setyasih (Heart Science Journal, 2024)
Background: Coronary artery disease (CAD) is a common type of heart disease that elevates the risk of morbidity and mortality significantly. Although revascularization techniques like coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) are advised for CAD patients, some people may not be eligible for or choose not to undergo revascularization. Even though cardiac rehabilitation (CR) enhances cardiovascular outcomes, quality of life, and general well-being, the utilization of CR is still very low.Case illustration: The first patient was a 72-year-old man, and the second patient was a 60-year-old man. They were referred for CR after refusing revascularization, and both are left-main and three-vessel disease patients. The first patient underwent CR for six months and the second patient for 18 months, then the Six Minutes Walking Test (6MWT) and 36-Item Short Form Health Survey (SF-36) were performed before and following CR. The evaluation is an increase in walking distance and patient quality of life.Conclusion: By enhancing quality of life, exercised-based CR programs offer an approach to managing CAD, especially in those who may not be suitable candidates for or choose to avoid revascularization procedures.